Echocardiographic characteristics and clinical outcomes in fetuses with pulmonary stenosis or pulmonary atresia with intact ventricular septum - Chengcheng Pang; Yingyu Wang; Junjun Shen; Liuqing Yang; Yufen Li; Wei Pan (Pediatrics and Neonatology)
Objective: To summarize echocardiographic characteristics of the anatomy and hemodynamic and clinical outcomes in fetuses with isolated pulmonary stenosis (PS) or pulmonary atresia with intact ventricular septum (PA/IVS). Methods: This was a single-center retrospective study of fetuses with isolated PS or PA/IVS. Echocardiographic variables and clinical outcomes after delivery were evaluated and compared. Results: Between 2016 and 2021, 115 livebirths with isolated PS or PA/IVS were included. Proportion of fetuses with mild, moderate and critical PS and PA/IVS was 41.7 %, 18.3 %, 26.1 % and 13.9 %. Fetuses with more severe PS had worse anatomic and hemodynamic profiles. Specifically, the cardiothoracic ratio, pulmonary valve (PV) velocity, degree and velocity of tricuspid regurgitation increased as PS severity increased; and the pulmonary artery/aorta ratio, right ventricle/left ventricle long-axis (TV/MV) ratio, tricuspid valve/mitral valve annulus (TV/MV) ratio, and tricuspid valve inflow duration/cardiac cycle ratio decreased as PS severity increased (P <0.001 for all). PV velocity ≥2 m/s predicted PV pressure ≥40 mm Hg after delivery, with an AUC of 0.81; TV/MV ratio combined with RV/LV ratio predicted clinical outcomes, with an AUC of 0.88. Live births with more severe PS had higher mortality rate (mild 0 vs. moderate 0 vs. critical 11 % vs. PA-IVS 36 %) and lower rate of developing bi-ventricles (mild 100 % vs. moderate 95 % vs. critical 89 % vs. PA-IVS 36 %). Conclusion: Findings of this study help better understand the anatomy and hemodynamic and clinical outcomes in fetuses with isolated PS or PA/IVS, which could have implications for prenatal counseling and prediction of fetal outcome.